2013
DOI: 10.1159/000352070
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensinogen Gene Polymorphisms and Angiogenic Factors with Preeclampsia in Chinese Women

Abstract: Objective: To investigate the association of angiotensinogen (AGT) gene polymorphisms and angiogenic factors with preeclampsia (PE) in Chinese women. Methods: A study on Chinese women was performed. Detection of the M235T polymorphism of AGT gene was carried out by PCR. Using a χ2 test, genotype and allele frequencies were compared in all groups. Maternal serum levels of vascular endothelial growth factor (VEGF) and placental growth factor (PlGF) and soluble fms-like tyrosine kinase 1 (sFlt1) at ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The mechanism by which the cytokine is able to directly trigger uterine contractions appears to be the activation of the arachidonic acid cascade, with consequent production of prostaglandin E 2 [18,19,20] . As for possible causes other than infection for an increased release of cytokines able to trigger gestational inflammation, it has been shown that genetic proinflammatory cytokine polymorphisms are associated with a higher risk of preterm birth [21,22,23,24] . Whatever the cause, IL-6 elevation cannot be considered to be a benign state [25], suggesting a search for suitable therapies aimed at reducing its concentration, in order to prevent dangerous prostaglandin release.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which the cytokine is able to directly trigger uterine contractions appears to be the activation of the arachidonic acid cascade, with consequent production of prostaglandin E 2 [18,19,20] . As for possible causes other than infection for an increased release of cytokines able to trigger gestational inflammation, it has been shown that genetic proinflammatory cytokine polymorphisms are associated with a higher risk of preterm birth [21,22,23,24] . Whatever the cause, IL-6 elevation cannot be considered to be a benign state [25], suggesting a search for suitable therapies aimed at reducing its concentration, in order to prevent dangerous prostaglandin release.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, irrespective of the strength of the economy, PE appears to be a predominant factor responsible for the increased morbidity and mortality among pregnant women and their newborns [2,3]. Although a key issue in obstetrics, the etiology and pathogenesis of PE have not yet been fully elucidated, making the prevention and the treatment of this disease difficult [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, overactivation of the oxidation reaction leads to oxidative stress. Experimental evidence implicates oxidative stress-induced endothelial dysfunction as the major pathology in PE [16,17,18]. For example, activation of the Gadd45/P38 MAPK pathway can cause an increase in oxidative stress, which might lead to PE [19].…”
Section: Discussionmentioning
confidence: 99%